Penentuan Pembelajaran untuk Meningkatkan Hafalan Al-Qur’an Menggunakan Metode MFEP - Fauzan Azim; Sarjon Defit; Gunadi Widi Nurcahyo (SEULANGA SYSTEM PUBLISHER, 2021)
Memorizing the Al-Qur'an is not as easy as expected, but it needs effort and interest in improving the memorization of the Qur'an, because there are still many students from the Modern Diniyyah Islamic Boarding School who are still unable to focus on improving their memorization due to various reasons. , such as a busy schedule of activities, laziness, and other factors. To improve memorization of the Al-Qur'an, there are many methods that can be used, but there are still many students who do not understand the correct method in improving Al-Qur'an memorization. The data processing in this study is qualitative, because this study focuses on the process of identifying appropriate learning in improving the memorization of the Al-Qur'an for students in Islamic boarding schools. Sources of data in the study were obtained from primary data, data were obtained directly from data sources, namely the ustadz who was given the mandate as the person in charge of this program. In addition, the data source in this study is secondary, because the data obtained is in the form of data in the form of documents related to real implementation. Furthermore, the data is processed using the Multifactor Evaluation Process (MFEP) method. MFEP is a method that can be used in decision support systems that use a 'weighting system' and this research uses the VB.NET 2017 programming language and MySQL. The results of the calculation have an accuracy rate of 80%, so this research can be used as a recommendation to improve the memorization of the Qur'an.